Pengaruh Organizational Citizenship Behavior, Stres Kerja dan Kompensasi Terhadap Kinerja Karyawan Besi UD Baja Logam - Yuniarga, Wanda; Mahmud, Mahmud (Jurnal Ekonomi dan Bisnis, 2023)
The primary objective of this study is to conduct an empiricalinvestigation into the impact of organisational citizenship behaviour,work stress, and compensation on the performance of employees at UdSteel Metal. The research sample consists of a total of 31 employees,representing the population under study. The study utilised a samplesize of 31 participants. The methodology employed for sample selectioninvolves the utilisation of saturated sampling. The findings of thisresearch demonstrate that each of the independent variables,specifically organisational citizenship behaviour, work stress, andcompensation, exert a positive and statistically significant impact onemployee performance (Y), either individually or collectively. Thecoefficient of determination indicates that 99.3 percent of the variancein employee performance can be accounted for by the variables oforganisational citizenship behaviour, work stress, and compensation.The remaining 0.7 percent of the variance is attributed to othervariables that were not included in this study.Penelitian ini bertujuan guna menguji secara empiris pengaruhorganizational citizenship behavior, stres kerja dan kompensasiterhadap kinerja karyawan besiUd Baja Logam. Populasi penelitian iniadalah seluruh karyawan yang berjumlah 31 karyawan. Sampel yangdigunakan dalam penelitian ini adalah 31 responden. Teknik penentuansampel menggunakan sampling jenuh. Temuan penelitian inimenunjukkan bahwa variabel independen, khususnya perilakukewargaan organisasi, stres kerja, dan kompensasi, memberikan dampakpositif dan signifikan secara statistik terhadap kinerja karyawan (Y),baik secara individu maupun kolektif. Koefisien determinasimenunjukkan bahwa 99,3 persen varian kinerja karyawan dapatdijelaskan oleh variabel perilaku kewargaan organisasi, stres kerja, dankompensasi. Sisanya 0,7 persen dari varian dikaitkan dengan variabellain yang tidak termasuk dalam penelitian ini. Keywords:Organizational Citizenship Behavior,Job Stress And Compensation,Employee Performance